2004
DOI: 10.1113/jphysiol.2003.058321
|View full text |Cite
|
Sign up to set email alerts
|

Indirect sensing of insulin‐induced hypoglycaemia by the carotid body in the rat

Abstract: The most physiologically important sensors for systemic glucoregulation are located in extracranial sites. Recent evidence suggests that the carotid body may be one such site. We assessed rat carotid body afferent neural output in response to lowered glucose, indirectly by measurement of ventilation, and directly by recording single or few-fibre chemoafferent discharge, in vitro. Insulin (0.4 U kg −1 min −1 )-induced hypoglycaemia (blood glucose reduced by ca 50% to 3.4 ± 0.1 mmol l −1 ) significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
100
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 69 publications
16
100
3
Order By: Relevance
“…This is not necessarily consistent with previous notions that hypoglycemia stimulates chemoafferent activity, or that it increases _ V E and ventilatory responses to hypoxia or hypercapnia [32][33][34]. The carotid bodies are believed to be important sensors for hypoxia and hypoglycemia, whose action is based on an insulin-induced severe hypoglycemia [35]. However, by using carotid body chemoreceptor cells, Conde et al [36] demonstrated that hypoxia-evoked release of catecholamine and hypoxiainduced action potentials of the carotid sinus nerve were identical under normal and low glucose concentrations.…”
Section: Fed/fasted Variation In Ventilatory and Metabolic Responses supporting
confidence: 74%
“…This is not necessarily consistent with previous notions that hypoglycemia stimulates chemoafferent activity, or that it increases _ V E and ventilatory responses to hypoxia or hypercapnia [32][33][34]. The carotid bodies are believed to be important sensors for hypoxia and hypoglycemia, whose action is based on an insulin-induced severe hypoglycemia [35]. However, by using carotid body chemoreceptor cells, Conde et al [36] demonstrated that hypoxia-evoked release of catecholamine and hypoxiainduced action potentials of the carotid sinus nerve were identical under normal and low glucose concentrations.…”
Section: Fed/fasted Variation In Ventilatory and Metabolic Responses supporting
confidence: 74%
“…The responsiveness of mammalian CB cells to hypoglycemia has been confi rmed in the in vitro CB-petrosal ganglion preparation (Zhang et al 2007 ) and in dispersed cat glomus cells (Fitzgerald et al 2009 ). Nonetheless, other authors have failed to fi nd any responsiveness of explanted whole CB preparations to low glucose (Bin-Jaliah et al 2004 ;Conde et al 2007 ) or any signifi cant changes in cytosolic [Ca 2+ ] in dispersed glomus cells in response to rapid glucose removal (Gallego-Martin et al 2012 ). In contrast to these last observations, we have found that, as in the rat (Garcia-Fernandez et al 2007 ), human glomus cells can also depolarize and release transmitters in response to a decrease in the extracellular glucose concentration (Ortega-Saenz et al 2013 ).…”
Section: Cellular Responses To Hypoglycemiacontrasting
confidence: 70%
“…In fact, several studies carried out in intact animals have claimed that the CB is indeed a glucose sensor, having a role on glucose homeostasis (2,32,51,54). Unfortunately, there is a nearly even number of studies performed both in intact animals and in intact isolated CB preparations denying the role of chemoreceptor cells as glucoreceptors (1,4,5,11,52). Without neglecting a role for the CB in glucose homeostasis, the concept on contention is the nature of the CB as a glucoreceptor.…”
mentioning
confidence: 94%